Profile and prognosis of patients with heart failure with recovered ejection fraction. (3rd October 2022) - Rocamora-Horrach, M; Peiro, O; Serrano, I; Rodriguez, J; Carrasquer, A; Ferrero-Guillem, M; Romeu, A; Lal-Trehan, N; Sanchez, R; Del Moral, V; Delgado, J R; Bardaji, A
Abstract: Background: Patients with heart failure (HF) and reduced ejection fraction (rEF) have a poor prognosis. Nevertheless, in the subgroup of patients with recovered ejection fraction (recEF) prognosis is unknown. Purpose: To analyze characteristics and prognosis in patients with HFrEF (initial EF and at one year <40%) and HFrecEF (initial EF <40% and at one year ≥40% with ≥10% absolute improvement from the initial value). Methods: Retrospective observational study of outpatients referred to the HF unit within March/2006 and November/2021. Baseline characteristics, ecocardiographic data and follow-up were collected, discerning between patients with HFrEF and HFrecEF. Results: A total of 346 patients (76.0% men) were analyzed with a mean of age 66.3 (IQR 57.8–74.4) years, of which 50.6% remained with rEF and 49.4% recEF. Median follow-up was 4.6 (2.8–7.9) years. Both groups had a similar risk profile albeit less prevalence of dyslipidemia in the group with recEF (43.5% vs 56.7%, p=0.015). Ischemic etiology predominated in those with rEF (41.7% vs 25.7%, p=0.002) and enolic in recEF (10.5% vs 3.4%, p=0.009). The incidence of combined event (readmission for HF or death) was lower in HFrecEF (33.6% vs 66.4%, p<0.001), as well as death (33.9% vs 66.1%, p<0.001) and readmission for HF (24.4% vs 75.6%, p<0.001). Prevalence of cardiovascular death was lower in the group with recEF (37.8% vs 61.1%, p=0.021). In the multivariate analysis, rEF was an independent predictor for the combined event (HR 2.17; 95% IC [1.45–3.25], p<0.001), as well as for global mortality and readmission for HF. Conclusion: Patients with HFrecEF have a similar risk profile than patients with HFrEF although with better long-term prognosis. Funding Acknowledgement: Type of funding sources: None.